Hubungan Gaya Kepemimpinan Demokratis Kepala Sekolah Dengan Kinerja Guru SD - Sudarto Sudarto; Asriadi Asriadi; Amaliah Amaliah (Universtas Negeri Makassar, 2023)
This study is a quantitative study with a correlational design that aims to determine whether there is or there is not a correlation between the democratic leadership style of the principal and the performance of elementary school teachers in Walenreng Village. The population in this study were all teachers at SD Walenreng who were also sampled with a total of 32 teachers. Based on the results of descriptive statistical analysis, the results of research on the democratic leadership style of principals have an average of 85.53 and a percentage of 68.425% in the good category and teacher performance has an average of 82.625 and a percentage of 66.1% in the good category. Based on the results of inferential statistical analysis, the tcount value (3.95102) is greater (>) the ttable value (1.69726) at the 5% significance level. Thus H0 is rejected and H1 is accepted. The results obtained in this study are that there is a significant relationship between the principal's democratic leadership style and teacher performance at Walenreng Elementary School, China District, Bone Regency.